Dyslipidemic and Protective Effects of Aspirin and Clopidogrel in Obese Rats - Ibrahim, Doa'a Anwar (International Journal of Pharmaceutical Sciences and Research, 2018)
Introduction: Antiplatelets play a crucial role in improving many metabolic disorders and complications, including dyslipidemia, atherosclerosis, diabetes mellitus and cardiovascular diseases. The most common and effective antiplatelets used widely are aspirin and clopidogrel. The aim of this study is to evaluate the dyslipidemic and protective effects of aspirin and clopidogrel in obese rats. Materials and methods: 24 rats were divided into two groups, control (n = 6) (was taken normal chow) and the other group (n = 18) were allowed to eat beef tallow (90 g) and saturated fat (10 g) for 6 weeks to induce obesity. The second group was further classified to three subgroups, subgroup I (n = 6) was kept as obese group (n = 6) (positive control), subgroup II (n = 6) obese rats were treated with aspirin and subgroup III (n = 6) obese rats were treated with clopidogrel for 7 days. At the end of experiment blood samples were taken and lipid profile, FBS measured as well as body weight and the relative weights of liver were calculated. Histopathological samples were taken from different organs including liver, kidneys and heart. Results: Outcomes of this study showed that both tested drugs had dyslipidemic and protective effects as they significantly reduced cholesterol, TG, FBS as well as body and liver weight. They also ameliorated obesity-induced abnormalities in histopathological tissues with slight differences between the tested groups. Conclusion: It suggested from the findings of this study that both aspirin and clopidogrel might have dyslipidemic and protective effects in obese rats supported by histopathological findings.